1997
DOI: 10.1161/01.cir.96.1.246
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Awake Respiratory Patterns Are Common in Chronic Heart Failure and May Prevent Evaluation of Autonomic Tone by Measures of Heart Rate Variability

Abstract: Breathing disorders are surprisingly common in awake patients with poor left ventricular function and produce large VLF oscillations in heart rate variability. If measures of heart rate variability are used for prognostic purposes during both short-term and long-term recordings, the confounding effects of variable respiratory patterns should be excluded. Respiratory rehabilitation might help control potentially hazardous surges in sympathetic tone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
2
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(146 citation statements)
references
References 25 publications
7
132
2
5
Order By: Relevance
“…17,18 The apparent role of slow and regular breathing as an active component in relaxation exercises, raises the hypothesis that routinely performed sessions of breathing exercises, as the sole intervention, may lead to a sustained reduction in BP. No attempt has been made in the past to test this hypothesis.…”
Section: Journal Of Human Hypertension (2001) 15 263-269mentioning
confidence: 99%
“…17,18 The apparent role of slow and regular breathing as an active component in relaxation exercises, raises the hypothesis that routinely performed sessions of breathing exercises, as the sole intervention, may lead to a sustained reduction in BP. No attempt has been made in the past to test this hypothesis.…”
Section: Journal Of Human Hypertension (2001) 15 263-269mentioning
confidence: 99%
“…In contrast, other authors [15][16][17] reported reduced HRV in CHF patients with a predominance of sympathetic activity. These authors suggest that sympathetic hyperactivity in HR control is a reflection of compensatory changes in the autonomic system caused by the evolution of the disease and aimed at ensuring homeostasis with an appropriate increase in cardiac output.…”
Section: Impact Of the Cardiorespiratory Diseases On Hrv At Restmentioning
confidence: 71%
“…Musialik-Lydka, Sreidniawa and Pasyk 12 , Tulppo and Huikuri 13 and Rosen et al 14 suggest the predominance of sympathetic activity in the sinus node. In contrast, van de Borne et al 15 , Ponikowski et al 16 and Mortara et al 17 observed the sympathovagal imbalance of the autonomic control of HR without evidence of sympathetic hyperactivity.…”
Section: Introductionmentioning
confidence: 91%
“…These multiple variables affecting heart rate variability, as well as the technical limitations in heart rate variability measurement, limit its potential to detect changes in cardiac sympathetic activity that may alter response to adjustment of medical therapy. 52,53 In studies directly comparing heart rate variability to I-123 MIBG imaging, I-123 MIBG imaging was predictive of all-cause mortality 54 and for either cardiac death or hospitalization for HF, 55 whereas heart rate variability was not.…”
Section: Alternative Methods For Assessment Of Cardiac Sympathetic Nementioning
confidence: 99%